Research of Flow Field of Alkaline/Surfactant/Polymer Solution in the Annular Depressurization Slot by PIV Experiment - Cheng Fu; Tingting Zhu; Di Wu; Ying Wang; Bin Huang (International Journal of Polymer Science)
In order to study the flow field changes of ASP (alkaline/surfactant/polymer) solutions with different molecular weights and flow rates when flowing through the annular depressurization slot in the laboratory, the annulus pipeline model was designed based on the principle of similarity. The particle image velocimetry (PIV) system was used to continuously capture the transient images when the ASP solution flows in the model under different experimental conditions. Tecplot software was used to analyze and process the nephrograms of the velocity distribution of ASP solution when flowing through the partially pressured injection tool with different depressurization slots. The experimental results showed that the vortex occurred at the bottom of the depressurization slots; the greater the flow rate, the closer the vortex center to the outer wall; higher molecular weight of the polymer in the ASP solution caused larger velocity gradient towards the wall. The number of the slots has no significant effect on the position of the vortex. This experiment provides a new research method for the velocity distribution of the internal flow field in the partially pressured injection tool.